Blaschkitis in children: a new entity? - Denk, Katharina; Flux, Katharina (Journal der Deutschen Dermatologischen Gesellschaft, 2011)
Blaschkitis is an acquired, rare dermatitis that follows the lines of Blaschko. Many consider blaschkitis as a variant of lichen striatus, although authors felt that it is a separate entity. A 2½-year-old girl presented with multiple grouped papules along the lines of Blaschko on her trunk. The main differences to lichen striatus are illustrated. Our case supports the hypothesis that blaschkitis is an entity of its own.
First published: 16 December 2010
Gesehen am 09.05.2022